Conserved orthology in termite chemosensory gene families - Johny, Jibin; Diallo, Souleymane; Lukšan, Ondřej; Shewale, Mayuri; Kalinová, Blanka; Hanus, Robert; Große-Wilde, Ewald (Frontiers in Ecology and Evolution, 2023)
Termites are eusocial insects known to use a variety of pheromones in tasks necessary for maintenance of their societies. As such, olfaction and pheromone communication in termites has been an object of intense study; trail-following pheromones (TFPs) and sex-pairing pheromones (SPPs), for example, have been identified in many termite species. In contrast, the molecular basis of olfactory detection is understudied in the group. Here, we present chemosensory genes of three species of termites belonging to three distinct lineages, Neotermes cubanus (Kalotermitidae), Prorhinotermes simplex (Rhinotermitidae), and Inquilinitermes inquilinus (Termitidae). Using antennal transcriptome screening for the identification of chemosensory genes allowed us to perform phylogenetic analysis. We found a comparatively large repertoires of odorant receptors (ORs), ionotropic receptors (IRs), odorant binding proteins (OBPs), chemosensory proteins (CSPs) and sensory neuron membrane proteins (SNMPs). The evolutionary analysis of termite chemosensory genes revealed Isoptera-specific expansions with a 1:1 orthologous pattern, indicating the existence of conserved olfactory functions. Our findings on basal eusocial insects will further enhance our understanding of the molecular underpinnings of eusociality and the evolution of olfactory communication in termites.